Analisis Kinerja Anggaran Program Penyelenggaraan Pemilihan, Pengangkatan dan Pemberhentian Kepala Desa : (Studi Kasus pada Dinas Pemberdayaan Masyarakat dan Gampong Kabupaten Aceh Barat) - Windari Sahputri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This study aims to analyze the budget program regarding the election, appointment and dismissal of village heads in the Community and Gampong Empowerment Office of West Aceh District. Every government agency in Indonesia has a budget, in accordance with “West Aceh District Regent Regulation Number 53 of 2016 Concerning Position, Organizational Structure, Duties, Functions, and Work Procedures of the Wes Aceh District Community Empowerment and Gampong Office” which states that “Public Empowerment Service and Gampong which is the implementing element of government affairs in the field of community and village empowerment which is the regional authority, where the Community Empowerment Service and Gampong have the task of assisting the regent